2009
DOI: 10.1002/elsc.200700040
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of tannery solid waste for protease production by Synergistes sp. in solid‐state fermentation and partial protease characterization

Abstract: Synergistes sp. DQ560074 produced a protease in submerged fermentation (SmF) at 400–420 U/mL and in solid‐state fermentation (SSF) at 745–755 U/g. The protease, which belongs to the aspartic protease class, was active over a wide range of pH (5–7) and at high temperatures (25–45°C). The protease is stable and active in various polar protic solvents (50% v/v) like ethanol, isopropanol, n–butanol, in polar aprotic solvents (50% v/v) like acetonitrile, and in non‐polar solvents (50% v/v) such as ethylacetate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Recently, the production of enzymes on solid state fermentation has been implemented in order to reduce the costs involved, especially if residues are used as substrates, and enhance the field of application (Sandhya et al, 2005;Kumar et al, 2009). However, there is indeed few research work developed on bench scale solid substrate fermentation, as the majority of this research was conducted on few grams of substrate materials,…”
Section: Enzymes Produced By Ssf Their Process Conditions and Applicmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the production of enzymes on solid state fermentation has been implemented in order to reduce the costs involved, especially if residues are used as substrates, and enhance the field of application (Sandhya et al, 2005;Kumar et al, 2009). However, there is indeed few research work developed on bench scale solid substrate fermentation, as the majority of this research was conducted on few grams of substrate materials,…”
Section: Enzymes Produced By Ssf Their Process Conditions and Applicmentioning
confidence: 99%
“…Therefore, these waste materials are creating a solid waste disposal problem in tanneries. Kumar et al (2009) studied the use of animal fleshings, the proteinaceous part of tannery solid wastes, as substrate for the production of aspartic protease by a Synergistes sp. It was suggested that there is a possibility to produce this enzyme by SSF using a cheap substrate and moreover, the enzyme obtained exhibited high stability in various organic solvents.…”
Section: Wastes Of Animal Originmentioning
confidence: 99%
“…Tanning industries generate approximately 1,50,000 tonnes of tanning wastes in the form of raw hide (and skin) trimmings, limed animal fleshings, hide splits and chrome shavings per annum during leather processing (Ganesh Kumar et al 2009). Tannery sludge contains plant macro and micronutrients especially nitrogen, phosphorus, iron, zinc and copper.…”
Section: Tanning Industry Wastementioning
confidence: 99%
“…Tanning industry is one of the highly polluting and growth-oriented industries and it generates approximately 1,50,000 tonnes of offal's in the form of raw hide (and skin) trimmings, limed animal fleshings, hide splits and chrome shavings per annum during leather processing (Ganesh Kumar et al, 2009). Animal fleshing (ANFL) is one of the major solid wastes that are generated during pretanning operations of leather processing.…”
Section: Introductionmentioning
confidence: 99%